MEMBANGUN KOMPETENSI ALUMNI DALAM MENGEMBANGKAN SOAL SOSIOLOGI BERBASIS LITERASI DAN NUMERASI - Joan Hesti Gita Purwasih; Seli Septiana Pratiwi; Deny Wahyu Apriadi (IKIP Siliwangi, 2022)
In generally, most of the training and mentoring of teachers is temporary. More intense and sustainable efforts are needed so that the teacher's abilities can continue to be developed. These efforts can be carried out by involving alumni who are already working as teachers. This continuous organization and quality assurance is also the responsibility of the Study Program in improving the quality of graduates and users. In addition, this is a way out that benefits various parties in improving the quality of human resources. The method used is a participatory method with alumni who are participants in the activity. Mentoring is carried out individually and in groups through mentoring techniques which are divided into concept delivery and preparation of literacy and numeracy-based assessments. As a result, alumni who work as teachers have proven their ability to develop an assessment prototype in the form of multiple choice questions based on literacy and numeracy. Mentoring pays attention to the structure of the content with a duration of 32 hours of lessons. The assistance provided also proves the ability of collaboration between study programs and alumni to ensure sustainable quality of human resources.